Spatial Changes in the Fluvial Landscape of the Bone River and Socio-Economic Impacts through Geospatial Technology Integration (Landsat-GIS) in the Gorontalo Region - La Ode Juni Akbar; Bambang Djau; Agung Djaba; Chyntia Dwi Faradiba; Daud Yusuf (Jurnal Penelitian Pendidikan IPA, 2025)
Changes in river systems can significantly impact communities, particularly through property and infrastructure losses. This study investigates the fluvial landscape changes of the Bone River and their socio-economic implications in the Gorontalo region from a spatial perspective. The research employs multi-temporal Landsat satellite imagery from the Google Earth Engine platform to analyze environmental dynamics in the study area over the period 1995–2025. The imagery dataset includes Landsat 5 TM (May 5), Landsat 7 ETM+ (February 17), Landsat 8 OLI/TRS (October 19), and Landsat 9 (May 31). The results indicate notable changes in the river’s course. Evidence of erosion and sediment deposition was identified along the Bone River banks. The patterns reveal a tendency toward lateral migration of the river channel, horizontal shifts, and narrowing of downstream segments. Several natural cut-off points have formed, along with shifts in the main channel in the upstream and midstream segments during the 1995–2025 period. The lateral migration of the river channel reached up to 1.2 km northeastward (N60°E), primarily driven by anthropogenic activities such as traditional sand mining along the western banks and the conversion of riparian land into residential areas. From a socio-economic perspective, these river morphological changes pose potential threats to riverside infrastructure and may trigger land-use conflicts, particularly in areas with active sand mining operations